Patient-specific instrumentation improves functional kinematics of minimally-invasive total knee replacements as revealed by computerized 3D fluoroscopy. (May 2020) - Shih, Kao-Shang; Lin, Cheng-Chung; Lu, Hsuan-Lun; Fu, Yang-Chieh; Lin, Cheng-Kai; Li, Song-Ying; Lu, Tung-Wu
Highlights: The 3D fluoroscopy method was used for accurate assessment of performance of PSI in MIS-TKA. Both PSI and non-PSI groups demonstrated good reconstructed rigid-body kinematics during functional activities. Patients with PSI-TKA demonstrated closer-to-normal rigid-body kinematics than those without PSI. Neither the PSI, nor the non-PSI groups showed normal contact patterns. Abstract: Background and objectives: Minimally-invasive total knee arthroplasty (MIS-TKA) has demonstrated very good short-term success, but its mid- to long-term results remain inconclusive. The success may be related to the tradeoff between a small incision and accurate positioning of the implant components. Patient-specific instrumentation (PSI) aims to improve the accuracy in restoring the knee axis and the clinical outcomes for MIS-TKA, but the results are yet to be confirmed by accurate assessment during functional activities. The purpose of the current study was to measure and compare the in vivo three-dimensional (3D) rigid-body and surface kinematics of MIS-TKA implanted with and without PSI during isolated knee active flexion/extension and sit-to-stand using state-of-the-art 3D model-based fluoroscopy technology. Methods: Ten patients treated for advanced medial knee osteoarthritis by MIS-TKA without PSI (non-PSI group) and nine with PSI (PSI group) participated in the current study. Each subject performed non-weight-bearing knee flexion/extension and sit-to-stand tasks while the motion of the prosthetic knee was under bi-plane fluoroscopy surveillance. The computer models of each of the knee prosthesis components were registered to the measured fluoroscopy images for each time frame via a novel validated 3D fluoroscopy method. Non-parametric 1-tailed Mann-Whitney tests were performed to detect the differences in the joint and surface kinematic variables every 10° of knee flexion between the non-PSI and PSI groups. The 1-tailed significance level was at α = 0.05. Results: The PSI group showed clear, coupled flexion/internal rotation during activities, while the non-PSI group remained roughly at an externally rotated position with slight internal rotations. The coupled rotation in the PSI group was accompanied by an anterior displacement of the medial contact and a posterior displacement of the lateral contact, which was different from the screw-home mechanism. Neither of the two groups showed the normal roll-back phenomenon, i.e., posterior translation of the femur relative to the tibia during knee flexion. Conclusions: With the state-of-the-art 3D fluoroscopy method, differences in both the rigid-body and surface kinematics of the prosthetic knees between MIS-TKA with and without PSI were identified. Patients with PSI demonstrated significant positive effects on the reconstructed rigid-body kinematics of the knee, showing clearer coupled flexion/internal rotations – an important kinematic characteristic in healthy knees – than those without PSI during activities with or without weight-bearing. However, none of them showed normal contact patterns. The current findings will be helpful for surgical instrument design, as well as for surgical decision-making in MIS total knee arthroplasty.